2021
DOI: 10.3390/biom11101542
|View full text |Cite
|
Sign up to set email alerts
|

Higher RET Gene Expression Levels Do Not Represent anAlternative RET Activation Mechanism in Medullary Thyroid Carcinoma

Abstract: This study was designed to investigate whether RET (rearranged during transfection) mRNA over-expression could be considered an alternative driver event for the development of medullary thyroid carcinoma (MTC), and if different RET isoforms could play a role in MTC tumorigenesis. Eighty-three MTC patients, whose mutational profile was previously identified by next-generation sequencing (NGS) IONS5, were included in this study. Expression analysis was performed by the quantitative reverse transcription-polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The RET proto-oncogene encodes a receptor tyrosine kinase that when activated either by a point mutation or gene rearrangement can result in a constitutively active cytosolic oncoprotein ( Mulligan, 2014 ; Chakravarty et al, 2017 ). Although RET mutations are well described in MTC ( Ciampi et al, 2019 ), there is a paucity of information about RET splice variants in MTC, though one study of a MTC cell line described three splice variants, RET 2/4, RET 2/5, and RET 2/6 and another described functional isoforms RET51 and RET9 ; however, neither played a role in MTC tumorigenesis ( Lorenzo et al, 1995 ; Mule et al, 2021 ). Our results demonstrate that irrespective of a driving mutation, there is a high frequency of RET splice variants in MTC, with all 25 MTCs in this study harboring at least one RET splice variant versus only 0.3% of 3,599 non-MTCs.…”
Section: Disscussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The RET proto-oncogene encodes a receptor tyrosine kinase that when activated either by a point mutation or gene rearrangement can result in a constitutively active cytosolic oncoprotein ( Mulligan, 2014 ; Chakravarty et al, 2017 ). Although RET mutations are well described in MTC ( Ciampi et al, 2019 ), there is a paucity of information about RET splice variants in MTC, though one study of a MTC cell line described three splice variants, RET 2/4, RET 2/5, and RET 2/6 and another described functional isoforms RET51 and RET9 ; however, neither played a role in MTC tumorigenesis ( Lorenzo et al, 1995 ; Mule et al, 2021 ). Our results demonstrate that irrespective of a driving mutation, there is a high frequency of RET splice variants in MTC, with all 25 MTCs in this study harboring at least one RET splice variant versus only 0.3% of 3,599 non-MTCs.…”
Section: Disscussionmentioning
confidence: 99%
“…The authors concluded that wild-type and alternatively spliced RET transcripts co-exist with rearrangements in PTC and may play a role in thyroid tumorigenesis. In MTC though, high RET gene expression levels have not been associated with an alternative RET activation mechanism ( Mule et al, 2021 ).…”
Section: Disscussionmentioning
confidence: 99%
See 3 more Smart Citations